Structure-property studies of a new one-dimensional Fe(III)/Mn(II) chain. (15th March 2020) - Zhang, Yuan-Zhu; Rath, Nigam P.; Cain, John M.; Meisel, Mark W.; Holmes, Stephen M.
Graphical abstract: The preparation, structure, and magnetic properties of a cyanide-bridged {[(pzTp)Fe III (CN)3 ][Mn II (phen)2 ][ClO4 ]· 1 /4 H2 O}n (1 ) chain is described. Magnetic studies indicate there is weak antiferromagetic exchange between the distorted Fe III LS ( S  = ½) and Mn II HS ( S  =  5 /2 ) spin centers and estimated g and J parameters of 2.06(2) and −0.92(1) cm −1 were found, respectively. Abstract: The preparation, structure, and magnetic properties of a one-dimensional chain, {[(pzTp)Fe III (CN)3 ][Mn II (phen)2 ][ClO4 ]} n (1 ), are described. It is readily obtained from methanolic solutions containing [NEt4 ][(pzTp)Fe III (CN)3 ]·H2 O, Mn II (ClO4 )·6H2 O, and two equivalents of 9, 10-phenanthroline. Magnetic data indicate that the low spin Fe III LS ( S  = ½) and high spin Mn II HS ( S  =  5 /2 ) ions experience weak cyanide-mediated antiferromagnetic exchange [ J iso  = −0.92(1) cm −1 and g iso  = 2.06(2)] owing to the presence of highly distorted Fe III ( μ -CN)Mn II units.